Activating low-temperature diesel oxidation by single-atom Pt on TiO2 nanowire array - Hoang, Son; Guo, Yanbing; Binder, Andrew J.; Tang, Wenxiang; Wang, Sibo; Liu, Jingyue (Jimmy); Tran, Huan; Lu, Xingxu; Wang, Yu; Ding, Yong; Kyriakidou, Eleni A.; Yang, Ji; et al. (Nature communications, 2020)
Supported metal single atom catalysts (SACs) present an emerging class of low-temperature catalysts with high reactivity and selectivity, which, however, face challenges on both durability and practicality. Herein, we report a single-atom Pt catalyst that is strongly anchored on a robust nanowire forest of mesoporous rutile titania grown on the channeled walls of full-size cordierite honeycombs. This Pt SAC exhibits remarkable activity for oxidation of CO and hydrocarbons with 90% conversion at temperatures as low as ~160 o C under simulated diesel exhaust conditions while using 5 times less Pt-group metals than a commercial oxidation catalyst. Such an excellent low-temperature performance is sustained over hydrothermal aging and sulfation as a result of highly dispersed and isolated active single Pt ions bonded at the Ti vacancy sites with 5 or 6 oxygen ions on titania nanowire surfaces. Supported metal single-atom catalysts face challenges on both durability and practicality. Here, the authors demonstrate that a sustained 90% diesel oxidation conversion at ~160 o C is achieved by single-atom Pt on TiO 2 nanowire-array integrated catalytic converter.